Effect of aquaculture on mercury and polyunsaturated fatty acids in fishes from reservoirs in Southwest China. (February 2020) - Jing, Min; Lin, Dan; Wu, Pianpian; Kainz, Martin J.; Bishop, Kevin; Yan, Haiyu; Wang, Rui; Wang, Qing; Li, Qiuhua
Abstract: Aquaculture can affect the polyunsaturated fatty acids (PUFA) and mercury (Hg) in fish by altering their diet. Here, planktivorous (silver carp and bighead carp), omnivorous and carnivorous fish with different dietary strategies were selected from two reservoirs, one with on-going aquaculture (WJD) and another without aquaculture (HF) in Southwest China. We compared the total mercury (THg), methylmercury (MeHg) contents and PUFA profiles of fish and their potential diets in these two reservoirs. THg and MeHg contents in omnivorous and carnivorous fish were lower from the WJD Reservoir, which is related to the lower THg and MeHg contents in the artificial fish food. THg and MeHg contents in silver carp from the WJD Reservoir were lower than those from the HF Reservoir, while they were similar in bighead carps from the two reservoirs. The Hg variation in planktivorous fish were inconsistent with that in plankton. THg contents in phyto- and zooplankton from the HF Reservoir were higher than those from the WJD Reservoir, yet their MeHg contents were similar. Artificial fish food which contained higher total PUFA eicosapentaenoic (EPA; 20:5n-3) and docosahexaenoic acid (DHA, 22:6n-3), significantly increased the total PUFA and EPA + DHA contents in carnivorous fish, but had less effect on that in omnivorous fish from the WJD Reservoir. Eutrophication caused by aquaculture reduced total PUFA and EPA + DHA contents of plankton in WJD, yet did not reduce those in planktivorous fish. The impacts of aquaculture on Hg and PUFA accumulated in fish were varied among different fish species, and the mechanism needs further exploration. Graphical abstract: Image 1 Highlights: Aquaculture decreased Hg and enhanced PUFAs contents in cultured fish. Eutrophication reduced PUFAs in plankton via changing the species composition. Hg and PUFAs in plankton can't predict Hg and PUFA bioaccumulation of planktivorous fish in on-going aquaculture reservoir. PUFA quality of cultured fish in eutrophic reservoirs was lower than that of fish from oligotrophic aquatic ecosystems.